Case report: Cochlear implantation was effective for progressive bilateral severe hearing loss associated with Kawasaki disease - Murakami, Daichi; Kimura, Takahito; Kono, Masamitsu; Sakai, Akihiro; Suenaga, Tomohiro; Hiraoka, Masanobu; Sakatani, Hideki; Ohtani, Makiko; Suzuki, Hiroyuki; Tokuhara, Daisuke; Hotomi, Muneki (Frontiers in Pediatrics, 2023)
Sensorineural hearing loss associated with Kawasaki disease has been increasingly reported, but its etiology remains unclear. Most reported cases of sensorineural hearing loss associated with Kawasaki disease have been mild and reversible during acute or subacute phases. However, severe bilateral hearing loss as a complication of Kawasaki disease can cause delays in cognitive and speech development. A four-year-old Japanese boy treated for Kawasaki disease had right-side moderate and left-side profound sensorineural hearing loss on the 141st day after onset of Kawasaki disease. Despite systemic steroid pulse treatment, hearing loss remained in both sides. After the recurrence of Kawasaki disease, hearing on the right side progressively worsened, meaning there was now severe hearing loss on both sides. Left cochlear implantation performed on the 1065th day after the onset of Kawasaki disease improved the patient's hearing and his ability to communicate. Sensorineural hearing loss associated with Kawasaki disease may progress over a long period and cause bilateral severe hearing loss, although past reports showed occurrence during acute or subacute phases. The clinical course of our patient suggests that intense inflammation caused by Kawasaki disease could be related to prolonged hearing loss. Cochlear implantation seems to be effective for sensorineural hearing loss associated with Kawasaki disease.